A 'Tale of two Jihadis'? Improperly conflating terrorists and foreign fighters in the Arab spring. (2nd April 2020) - Schumacher, Michael J.; Schraeder, Peter J.
ABSTRACT: This article draws on a unique dataset of state-level data for 196 countries to establish answers to three research questions. We begin by exploring whether a global spike in terrorist acts and the numbers of foreign fighters leaving to fight for ISIS in Syria and Iraq are linked during the first five years of the Arab Spring (2011–15). We also assess whether the spike in terrorist attacks and foreign fighters for ISIS can be labeled a phenomenon of the Middle East and North Africa and Islam more generally. In other words, are we witnessing a 'Tale of Two Jihadis'? The answer to both questions is 'no.' Third, we seek to establish whether terrorist acts and foreign fighters are driven by the same explanatory factors, as would be assumed by those who conflate the two phenomena. A series of negative binomial regressions demonstrates that while a country's level of domestic political instability leads to increases in both foreign fighters and terrorist attacks, the explanatory commonalities end there. Whereas foreign fighters to ISIS hail from Muslim majority countries with higher levels of education and internet access, terrorist attacks occur in countries with lower levels of unemployment and higher levels of ethnic fractionalization.